Advertising in Translation: English vs. Greek - Sidiropoulou, Maria (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractThe role of advertising can be perceived quite differently across cultures. Analysts, therefore, are advised to approach advertisements with some understanding of the expectations in a particular culture (Rotzoll 1985). Such advice is particularly important in translating advertisements since the various strategies and techniques employed for persuasion have to be adjusted in the target culture in order for the intended perlocutionary effect to be achieved. The 55 English-Greek advertisement pairs examined in this research indicate that the translator should be sensitive not only to conventions applying across genres in a particular culture, but also to conventions associated with genre-internal variation, as 'soft-sell' and 'hard-sell' approaches in advertising are shown to require different types of interferences, in the translation process, for appropriateness to be achieved.